2018
DOI: 10.18506/anemon.347913
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye İslami Piyasalarında Ramazan Ayı Etkisi

Abstract: Bu çalışma kapsamında Ramazan ayının Türkiye İslami piyasalar üzerindeki etkisi incelenecektir. Türkiye İslami piyasalarını temsilen BİST tarafından hesaplanan Katılım 30 (KAT30) endeksi, ele alınmış ve bu endekse ait 17 Şubat 2011 ile 30 Aralık 2016 tarihleri arasındaki döneme ilişkin günlük getiriler kullanılmıştır. Çalışma da Ramazan Ayı on günlük dilimlere ayrılarak üç kukla değişken oluşturulmuş ve oluşturulan bu kukla değişkenlerin modeldeki etkisi incelenmiştir. Çalışmada 3 EGARCH modeli kurulmuştur; bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Findings indicated the effect to be significant and positive for just five sectors, with the average returns of some sectors being relatively higher than those of the BIST-100 during the month. Alsu et al (2018) found a Ramadan effect in BIST on Islamic markets for the daily returns of the Participation-30 Index between 17.02.2011 and 30.12.2016. Their findings revealed that there has been a decline in the second 10 days of Ramadan, due to investors' _____________________________________________________________________________________________________ DOI: 10.17261/Pressacademia.2020.1189 16 devoting themselves to religious rituals.…”
Section: Introductionmentioning
confidence: 94%
“…Findings indicated the effect to be significant and positive for just five sectors, with the average returns of some sectors being relatively higher than those of the BIST-100 during the month. Alsu et al (2018) found a Ramadan effect in BIST on Islamic markets for the daily returns of the Participation-30 Index between 17.02.2011 and 30.12.2016. Their findings revealed that there has been a decline in the second 10 days of Ramadan, due to investors' _____________________________________________________________________________________________________ DOI: 10.17261/Pressacademia.2020.1189 16 devoting themselves to religious rituals.…”
Section: Introductionmentioning
confidence: 94%